Association between red cell distribution width and 30-day mortality in patients with sepsis-associated liver injury: a retrospective cohort study - Ao, Ting; Huang, Yingxiu; Zhen, Peng; Hu, Ming (Frontiers in Medicine, 2024)
BackgroundSepsis-associated liver injury (SALI) is a critical component of sepsis-induced multiple organ dysfunction with high mortality. Identifying biomarkers for risk stratification is essential. Red cell distribution width (RDW), indicating variation in red blood cell volume, has been linked to adverse outcomes in various diseases. This study aimed to evaluate the association between RDW and 30-day mortality in SALI patients.MethodsA retrospective cohort study was conducted using data from the Medical Information Mart for Intensive Care-IV database. Patients admitted to the intensive care unit (ICU) with SALI were included. RDW was recorded within the initial 24 h. The primary outcome was 30-day mortality. A multivariable Cox regression analysis was performed to examine the relationship between RDW and mortality.ResultsAmong 529 SALI patients (mean age 68.7 years, 61.8% male), 46.1% had RDW > 15.5%. The 30-day mortality rate was 35.5%. RDW was significantly higher in non-survivors compared to survivors (17.2 ± 3.0 vs. 15.4 ± 2.3, P < 0.001). Cox regression identified RDW as an independent risk factor for 30-day mortality (HR 1.14, 95% CI 1.09 to 1.19, P < 0.001). Subgroup analyses demonstrated that the findings were consistent across the various groups.ConclusionElevated RDW is independently associated with higher 30-day mortality in patients with SALI, suggesting its potential role in risk stratification and clinical management.